The Role of Biologic Agent in The Management of Ankylosing Spondylitis : A Case Report - Gede Dilajaya Robin; Gede Kambayana; Robin, Gede Dilajaya (PT Dexa Medica, 2025)
Background: Ankylosing spondylitis (AS) is a chronic immune-related arthritis primarily affecting the spine, sacroiliac joints, and surrounding tissues. The estimated incidence of AS ranges from 1.30–1.56 million in Europe and from 4.63–4.98 million in Asia. However, data on the current prevalence of AS in Indonesia remains limited. Various treatmentmodalities are available, one of them are biological agents that play a significant role in managing disease progression and preventing complications. Case: A 25-year-old male presented with a four-year history of chronic back pain. Laboratoryresults showed an elevated C-reactive protein (CRP) level of 31.20 mg/dl. Pelvic and thoracolumbar X-ray showed kyphotic deformity, bamboo spine, and dagger spine appearance. The patient was diagnosed with high disease activity ankylosingspondylitis (ASDAS-CRP: 2.9). Initial treatment with nonsteroidal anti-inflammatory drug (NSAID) alone did not result in clinical improvement. Due to the severity of disease activity, combination therapy using NSAID and a tumor necrosis factor (TNF) inhibitor was used, and reported to give satisfactory clinical response. Additionally, patient also underwent corrective spinal surgery due to severe deformity. Conclusion: TNF inhibitors are currently considered as the first-line biological therapy in the management of ankylosing spondylitis, due to their superior efficacy and safety in controlling disease progression compared to other biological agents.